A Study on Anxiety, Facility, and Protective Measures of Health Professionals of Bangladesh - Sakibur Rahat; Nasrin Jabin; Sneha Sarwar; Tarak Aziz (Khazanah Sosial, 2021)
As part of the worldwide pandemic of SARS-CoV-2 infection, Bangladesh was infected. The firstthree cases were confirmed by the Institute of Epidemiology Disease Control and Research (IEDCR) in the first week of March 2020. The Bangladeshi government immediately required its citizens to comply with the national lockdown to curb the spread of a virus where everyone keeps themselves safe and protected at home except for medical professionals, who risk treating patients in a hospital. This article explores the situation medical professionals go through during the pandemic. This study used a quantitative method with a cross-sectional survey based on frequently asked questions (FAQ). Primary data were obtained from 200 respondents (doctors, nurses, medical professionals). According to the study, the lack of access and availability of PPE such as Particulate Respirator Masks, face shields, protective clothing, protective gloves, and hand sanitizer/disinfectant as facilities in hospitals causes Generalized Anxiety Disorder, Panic Disorder, Social Phobia, and Post-Stress Disorder Trauma from before. However, a positive correlation was found between lack of supply of protective equipment and increased anxiety, panic disorder, social phobia, etc., among healthcare professionals.